Drivers of atmospheric nitrate processing and export in forested catchments. Issue 2 (23rd February 2015) - Rose, Lucy A.; Sebestyen, Stephen D.; Elliott, Emily M.; Koba, Keisuke
Abstract: Increased deposition of reactive atmospheric N has resulted in the nitrogen saturation of many forested catchments worldwide. Isotope‐based studies from multiple forest sites report low proportions (mean = ∼10%) of unprocessed atmospheric nitrate in streams during baseflow, regardless of N deposition or nitrate export rates. Given similar proportions of atmospheric nitrate in baseflow across a variety of sites and forest types, it is important to address the postdepositional drivers and processes that affect atmospheric nitrate transport and fate within catchments. In a meta‐analysis of stable isotope‐based studies, we examined the influence of methodological, biological, and hydrologic drivers on the export of atmospheric nitrate from forests. The δ 18 O‐ NO 3 − values in stream waters may increase, decrease, or not change with increasing discharge during stormflow conditions, and δ 18 O‐ NO 3 − values are generally higher in stormflow than baseflow. However, δ 18 O‐ NO 3 − values tended to increase with increasing baseflow discharge at all sites examined. To explain these differences, we present a conceptual model of hydrologic flowpath characteristics (e.g., saturation overland flow versus subsurface stormflow) that considers the influence of topography on landscape‐stream hydrologic connectivity and delivery of unprocessed atmospheric nitrate to streams. Methodological biases resulting from differences in sampling frequency and stable isotope analytical techniques may further influence the perceived degree of unprocessed atmospheric nitrate export. Synthesis of results from numerous isotope‐based studies shows that small proportions of unprocessed atmospheric nitrate are common in baseflow. However, hydrologic, topographic, and methodological factors are important drivers of actual or perceived elevated contributions of unprocessed atmospheric nitrate to streams. Key Points: Percent atmospheric nitrate is low during baseflow in many forested catchments Percent atmospheric nitrate may be high during stormflow Catchment hydrology and topography influence atmospheric nitrate in streams